(untitled) (Journal of Dhaka Medical College, 2011)
A prospective cross sectional study was designed to assess the patterns of adult-onset epilepsy and determine the types of epilepsy which develop after complex febrile convulsion (CFC) and find out the causes of epilepsy, from January to December 2008, in Epilepsy Clinic of the Department of Neurology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. 106 consecutive adult (age>13 years) patients with adult-onset epilepsy receiving treatment from Epilepsy Clinic of the Department of Neurology of BSMMU, Dhaka, were the sample of this study. Records of these patients were reviewed & the patients & their family members were interviewed to assess the medical history. The data obtained from the records and the interviews formed the basis of this study. Chi-Square test was applied to analysis the data. Interviewed results and records of 106 patients were analyzed. Of the 106 patients with adult- onset epilepsy, the epilepsy categories [median age: 20 years, range: 14-46 years] were: generalized epilepsies in 51 (54.06%), partial epilepsies in 45 (47.7%), & undetermined epilepsies in 10 (10.6%) Thirty one (32.86%) of the 106 patients had history of CFC in the childhood (71% male, 29% female). Partial epilepsies were significantly associated with history of CFC [Odds Ratio: 3.29; (95% CI 1.30-8.06), (c2=5.49, df=1, p=0.012)] when compared to other epilepsies and epilepsy syndromes. An initial unprovoked simple partial seizure was also significantly associated with a positive history of CFC [Odds Ratio: 8.05; (95% CI 2.88-22.45), (c2=15.86, df=1, p<0.001)]. Generalized epilepsies are more common than partial epilepsies. Partial epilepsies seem to be associated with a history of CFC in childhood. The mechanism & pathophysiology of association between CFC and epilepsy in affected probands requires further investigations. Identification of the basic defect in relation to CFC & epilepsy may have important implication for the prevention of adult- onset epilepsy in patients with history of CFC. But the risk of epilepsy after febrile convulsions is much less than reported in many hospital studies & if febrile convulsion causes brain damage that leads to later epilepsy, this is a rare occurrence. Keywords: Generalized epilepsy; partial epilepsy; febrile convulsion; afebrile seizures; genetic. DOI: http://dx.doi.org/10.3329/jdmc.v20i1.8567 J Dhaka Med Coll. 2011; 20(1) :20-24